Improving the Professionalism of Education Personnel in Jambi Province Through Principal’s Supervision Skills - Habibie, M Fadly; Mukhtar, Mukhtar; Hidayat, Hidayat; Habi, Nuraida Fitri (Journal of Social Work and Science Education, 2023)
The purpose of this study is to improve school principals’ supervisory skills in order to increase the professionalism of education workers in Jambi Province. A descriptive qualitative technique is used in this descriptive qualitative research. Snowball sampling was used to identify research subjects, which included school principals, vice principals, and educational personnel. Data collection methods include observation, interviews, and documentation. SMAN in Jambi Province is the research location. The study’s findings are the supervisory skills of school principals in increasing the professionalism of education staff in Jambi Province, which include: a) planning through a work program determined by the principal’s policy, b) distributing education staff in their respective tasks, even if some are not according to their expertise, c) in carrying out work such as entering key school data into computers, filing correspondence, distributing correspondence, and storing school goods, and d) administrative work is still rarely supervised at SMA Negeri 1 Jambi City. The study’s conclusion is that administrative professionals must adhere to specified service operational criteria.